Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Pada Umkm Urban Kayoe - Dita Sukma Palupi; Siti Aisyah; Dwi Epty Hidayaty (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine the effect of human resource job satisfaction on employee performance at UMKM Urban Kayoe. Many factors affect employee performance, but factors that are rarely measured are the importance of performance and the quality of human resources. This study used a descriptive approach with data collection techniques using questionnaires and interviews. The number of samples in this study were 20 respondents. The data analysis technique used in this study uses descriptive data. The results showed that the quality of human resources had a significant positive effect on the importance performance of Urban Kayoe SMEs. The Quality of Human Resources has a significant positive effect on Employee Performance and Satisfaction at Urban Kayoe SMEs. Importance performance has a significant positive effect on employee performance and satisfaction at Urban Kayoe SMEs. The findings show that Urban Kayoe's performance in key areas is significantly influenced by the quality of its human resources. At UMKM Urban Kayoe, the quality of human resources significantly improves employee performance and satisfaction. Critical performance has a very beneficial impact.